Distribution and genetic diversity of Xylella fastidiosa associated with olive quick decline in southeastern Brazil - Safady, Nágela Gomes (2019)
Xylella fastidiosa (XF) is a bacterium capable of colonizing a large number of plants, but is mainly known to cause disease in economically important crops such as citrus, grapevines, coffee and more recently olive trees. XF colonizes the xylem vessels, forming biofilm and thus blocking the passage of sap and water from roots to leaves. General symptoms related to diseases caused by these bacteria are leaves wilt, burning and subsequent leaf necrosis, leaves chlorosis and in same pathosystem plant death. The bacterium, which until recently was restricted to the American continent, in 2013 was reported in southeast Italy causing severe symptoms in olive trees leaving to dead of over one milion plants and infected eleven million. This desease was call as Olive Quick Decline Syndrome (OQDS). Since then XF has also been reported in other European countries, such as France, Spain and Portugal, infecting sweet cherry, almond, lavender and ornamental plants. Lately, in mid-2016, similar symptoms as observed in disease olive plants in Italy were also found in olive plants in the state of Minas Gerais in Brazil. The identification of XF in symptomatic olive trees in Brazil leave us to some questions about the; geographic distribution of infected plants, genetic diversity of pathogen, and natural infectivity of possible vectors involved on natural transmission. Therefore, the objetives of this work were; 1. to analyze the distribution of XF in olive orchards in southeastern Brazil; 2. to determined the genetic diversity of strains isolated from symptomatic trees; 3. to verify the natural infectivity of possible vectors. Targeting the objectives 1 and 2 aproximatley 500 samples with OQDS-like symptoms were analized for the presence of XF by using specific primers and bacterial isolation in agar medium growth following the genetic diversity studies. Those samples were sampled from twenty-five orchards located in 15 cities of states of São Paulo and Minas Gerais plus one from Espirito Santo. XF was identified in 21 of the 26 orchards analyzed. A total of 204 isolates were cultured from the symptomatic samples. Twenty-one representative strains of whole population were typed by both Multilocus Sequence type (MLST) and Simple Sequence Reapts (SSR) and the total population by the last methodology. Sixty-five percent of strains were identified as ST16 (previsouly reported in coffee plants) but others already described such as ST70 (from in hibiscus) and ST13 (from citrus) were found causing OQDS in olive plants. Beside these, new STs like the 84, 85 and 86, all belonging to subsp. pauca of X. fastidiosa were also identified in disease olive plants. Population genetic analysis using twelve SSR markers clustered the total population (204 strains) from 16 different orchards representing 12 different municipalities in only three subpopulations. Except the strains from SPA1, MG18, MGA7, MG10 and MGA4 all the remaining strains were placed in a specific subpopulation. In the SPA1 (S22°42'10.71"/W45°41'32.91") was found the largest number of private alleles and heterozygosis and also two different STs (84 and 86). The unbiased heterozygosity (HNei), ranged from 0 to 0.53 (Avg 0.20). Analyzes of possible migration routes have shown the orchards MG-A1 and MG-A2 as the largest migrant donors. X. fastidiosa was detected in at least 37% of potential vectors in commercial orchard SP-A1.